Economic Consequences of Administering Obinutuzumab as a Short Duration Infusion in Italian Patients with Advanced Follicular Lymphoma: A Cost Analysis - Bellone, Marco; Pradelli, Lorenzo; Tavarozzi, Rita; Ladetto, Marco; Nepoti, Giuliana; Guardalben, Emanuele; Ghislieri, Daniela (Farmeconomia. Health economics and therapeutic pathways, 2022)
OBJECTIVE: To assess time- and cost-savings in relation to active time of health care professional (HCP) and resource consumption of administering obinutuzumab as a short duration infusion (SDI) in patients in treatment for Follicular Lymphoma (FL). METHODS: A cost-minimization model was developed to compare resource consumption and cost of the obinutuzumab SDI relative to obinutuzumab regular infusion rate (RIR) for the previously untreated and rituximab-refractory FL. Monetary valuation of resource and time allocated to treatment as a whole was carried out from the Italian Hospital and the societal perspective. Direct costs included HCP costs for drug preparation and administration activities, non-drug consumable costs, drug acquisition costs, and formal care costs. Indirect costs included the lost productivity of patients and informal caregivers. All costs (updated to 2021-value) were estimated by multiplying resource use by the unit cost of each resource. Evidence on resource use and unit costs were retrieved from scientific literature and standard Italian tariffs. A deterministic sensitivity analysis was used to test the results. RESULTS: The administration time of obinutuzumab SDI is shorter than with obinutuzumab RIR, with a difference of 102 minutes per patient and for every cycle of administration beyond the first one. On average, the cost of HCP time invested in the preparation and administration of obinutuzumab RIR is € 92 during cycle 2 and from cycle 2 onwards, compared to € 54 per cycle of obinutuzumab SDI. Overall, the cost from the societal perspective is estimated to be € 38,698 for obinutuzumab RIR and € 37,692 for obinutuzumab SDI, resulting in a cost-saving per patient of € 1,007 (2.6%). CONCLUSIONS: The application of obinutuzumab SDI schedule allows substantial reduction of hospital stay, improving quality of life of patient and caregiver and reducing costs and health care system burden. The time-savings with obinutuzumab SDI may improve clinical unit capacity by optimizing chair utilization and/or allowing rearrangements of the nurse residual time into valuable supplementary activities, spanning from more patient-centered clinical support to research and learning activity